2015
DOI: 10.1016/j.ijmm.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of silver and zinc nanoparticles against Vibrio cholerae and enterotoxic Escherichia coli

Abstract: Vibrio cholerae and enterotoxic Escherichia coli (ETEC) remain two dominant bacterial causes of severe secretory diarrhea and still a significant cause of death, especially in developing countries. In order to investigate new effective and inexpensive therapeutic approaches, we analyzed nanoparticles synthesized by a green approach using corresponding salt (silver or zinc nitrate) with aqueous extract of Caltropis procera fruit or leaves. We characterized the quantity and quality of nanoparticles by UV–visible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
177
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(182 citation statements)
references
References 97 publications
4
177
0
1
Order By: Relevance
“…144 However, studies have shown that NPs can act on the ion channels in bacterial biofilms, thereby regulating the metabolic activity of bacteria. Salem et al 145 showed that the amounts of Ag NPs and ZnO NPs necessary for growth inhibition (minimal inhibitory concentration assay) and for inhibition of metabolic activity (INT assay) were nearly equal. The result suggested that the dominant antimicrobial targets of the NPs are the metabolic pathways of bacteria.…”
Section: Nps Inhibit the Formation Of Bacterial Biofilmsmentioning
confidence: 99%
“…144 However, studies have shown that NPs can act on the ion channels in bacterial biofilms, thereby regulating the metabolic activity of bacteria. Salem et al 145 showed that the amounts of Ag NPs and ZnO NPs necessary for growth inhibition (minimal inhibitory concentration assay) and for inhibition of metabolic activity (INT assay) were nearly equal. The result suggested that the dominant antimicrobial targets of the NPs are the metabolic pathways of bacteria.…”
Section: Nps Inhibit the Formation Of Bacterial Biofilmsmentioning
confidence: 99%
“…In recent past nanoparticles have shown promising results to inhibit microorganisms and drug resistant microorganisms. Several studies conducted around the glove are reporting the antimicrobial properties of various nanoparticles such as silver, gold and zinc against a broad range of nanoparticles (Salem et al, 2015;Zhang et al, 2015;Thomas et al, 2014). However the activity of the particles can variety based on the method they are prepared and because of particle size.…”
Section: Antibiogram Studymentioning
confidence: 99%
“…[13] An earlier study exhibited that plant mediated synthesized Silver nanoparticles can inhibit the biofilm formation and reduce the threat of drug resistance. [14] The present study revealed that high antibacterial potential of silver nanoparticles was found against tested strains of P. aeruginosa even at very low concentration of AgNPs (in μg/ml) in comparison to plant extracts and reference drug used. Our findings also correlate with the study previously reported by researchers which evaluated the antibacterial effect of Silver nanoparticles against multi-drug resistant strains of P. aeruginosa.…”
Section: Discussionmentioning
confidence: 51%